A tech-driven, people-centered approach for the Batangan MetaMediatheque defining the library of the future through natural language processing and generative design - Cordez, Zeus Immanuel V. (College of Architecture, University of the Philippines Diliman, 2025)
The Filipino is a prolific digital citizen, and yet, beyond the bounds of a few emerging smart cities, there is a dearth of digitally-integrated public services within reach of the rest of the country. Within this context, a responsive comprehensive architectural design project aimed to create a baseline, locally-responsive multimedia library was undertaken. The pre-design phase hinged on research involving two Natural Language Processing algorithms: Sentiment Analysis (SentimentR model) and Generative Pre-trained Transformer-supplemented Thematic Analysis (GPT4-o model). The schematic design and design development phases were informed by generative design tools including Stable Diffusion for conceptual image production, and Hektar AI for massing and developmental control. (1) Democratic information access, (2) Tropical futurism, and (3) Plug-n-play modularity become the anchoring concepts of the mediatheque.